EXAMINING THE EFFECTIVENESS OF WHATSAPP IN FACILITATING ONLINE LEARNING - Nanan Abdul Manan; Badroeni Badroeni; Oman Hadiana (Indonesian Journal of Learning and Instruction, 2023)
This study aims to investigate and analyze the adaptation of teaching and learning processes in the Covid-19 era, focusing on the implementation and effectiveness of various technological tools and strategies. A qualitative research method was employed, utilizing observations and questionnaires to garner insights. A total of 232 respondents participated, predominantly comprising senior high school students from Kuningan District. The primary objective is to explore how educational institutions have innovated teaching and learning methodologies, emphasizing the utilization of technology, particularly WhatsApp, as a medium for facilitating education during the Covid-19 pandemic. Through a qualitative approach, the study utilized observations and questionnaires as instrumental tools for data collection. The findings revealed that online learning has emerged as a robust model in enhancing teaching and learning experiences across different educational stages, from early childhood to higher educational institutions. WhatsApp has been highlighted as a prevalent application, enabling teachers and students to navigate the challenges posed by the pandemic in the educational domain. Based on the findings, the study concludes that continuous inventive strategies are essential in teaching to adapt to changing scenarios and effectively respond to classroom needs. Furthermore, the integration of technology, like WhatsApp, in educational practices proves to be a valuable asset in overcoming the pandemic-induced challenges in education.